Distribution and dissolution kinetics of biogenic silica in sediments of the northern South China Sea - Ma, Yuwei; Yang, Bin; Zhou, Nan; Huang, Jin; Liu, Su Mei; Zhu, Dongdong; Liang, Wen (Frontiers in Marine Science, 2023)
The dissolution efficiency of sedimentary biogenic silica (bSiO2) dramatically affects the regeneration of dissolved silicic acid (dSi) at the sediment-water interface, which is a crucial pathway to maintain Si balance and silicic productivity growth in marine environment. We conducted wet alkaline leach and flow-through experiments to explore the dissolution behaviors of sedimentary bSiO2 in the northern South China Sea (NSCS) - one of the largest marginal sea continental shelves. The contents of bSiO2 in surface sediments were 0.64 - 2.06%, with an average of 1.04 ± 0.35%, varying with isobath of water depth. The solubility of bSiO2 in surface sediments ranged from 227 μmol L-1 to 519 μmol L-1, and the dissolution rate constants varied from 0.67 to 1.53 yr-1 under specific conditions in lab incubation. The correlation between the biogenic materials (bSiO2, OC, TN) revealed a different preservation pattern of bSiO2 in finer (Φ > 5.5) and coarser (Φ < 5.5) sediments. The high concentration of Al in sea water and “Al – detrital – bSiO2” interactions in sediments significantly interfered the apparent solubility and dissolution dynamics of bSiO2. We combined the regional characteristics (primary production, bottom current, resuspension-deposition) and the reconstructed dissolution kinetics of bSiO2 explained the mismatch between the surface (diatom biomass)/(total phytoplankton biomass) ratio and the sedimentary bSiO2/OC ratio, and the mismatch between the surface bSiO2 primary productivity and the bSiO2 sediment records in the NSCS. The resuspension-deposition and the higher reconstructed rate constants (0.94 ± 0.13 yr-1), dissolution rate (0.20 ± 0.01 yr-1) were responsible for the lower bSiO2/OC ratio (0.45 ± 0.28) in the inner-shelf, and the winnowing process in the outer-shelf with the lower reconstructed reactivity (0.30 yr-1), dissolution rate (0.001 yr-1) led to the well preservation of bSiO2 in the upper-slope. Furthermore, through the comparison with other sea areas, the relatively lower reactivity (1.12 ± 0.3 yr-1) of bSiO2 in sediments support the NSCS sediments may serve as an important silica sink in the world ocean silica cycle.